Analysis of employment conditions and management training needs among medical caregivers (医疗护理员从业现况及管理培训需求分析) - WANG Huaxin (王华新); LIU Guiying (刘桂英); TANG Ling (唐玲); E Haiyan (鄂海燕); GAO Bo (高波); SUN Mingli (孙明丽); ZHOU Jie (周洁); WANG Xiao (王潇) (中西医结合护理)
Medical caregivers as auxiliary medical care personnel have become an indispensable labor supplement in nursing work. Given the public's rising awareness of health and rights protection, the quality of patients' nursing staff has also improved accordingly. In order to strengthen life care skills and professional quality, it's required to standardize professional training. However, there are still many problems in the training of medical nursing staff and content in China. This article analyzed the current employment conditions, management and training needs of medical caregivers, aiming to provide reference for further establishment of standardized training curriculums. (医疗护理员是辅助医疗护理的人员, 已成为护理工作中不可缺少的劳务补充。为加强护理员生活照护技能和职业素养, 需对医疗护理员进行规范化专业培训。目前, 国内关于医疗护理员的培训方式和内容尚存在着诸多问题。本文就医疗护理员目前的从业、管理和培训状况进行分析, 为进一步设置规范化的培训课程提供参考。)